Study on Pregnancy Outcomes in Intrauterine Insemination Cycles with Motile Spermatozoa Insemination (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Intrauterine Insemination (IUI) is one of the most common assisted reproductive technology methods in the world to treat various forms of infertility. The influence of number of IUI applied with the percentage of motile spermatozoa during insemination is critical on the likelihood of a successful pregnancy. The aim of our study is to assess the results of IUI as a function of the number of IUI applied with motile spermatozoa inseminated during intrauterine insemination in couples with infertility.Materials and methods: This is a prospective study conducted in Surgiscope Fertility Centre, Chattogram, Bangladesh over 21 months on 596 couples who underwent IUI from 01/12/2017 to 30/09/2019. We performed semen analysis of the male partner from the couples who underwent IUI, calculated the sperm motility and the relationship between number of IUI applied with motile spermatozoa and the pregnancy rate of IUI. Multiple variables were selected such as, patient parameters like age of female, number of IUI, percentage of motile spermatozoa inseminated, endometrial thickness and ovulation induction protocol which were recorded and statistically analyzed.Results: Among the 596 patients, the overall success rate was 11%. The maximum number of successes were observed in patients with 3 IUI applications whereas the success rate was lower in comparison with decreasing IUI applications. The regression between the success and number of insemination and age indicate that there is a statistically significant positive relationship between number of inseminations completed and the rate of successful pregnancy, but no significant relationship between the number of prewash sperm and successful pregnancy. These could be due to lower population size. As an ovulation inducing agent, a 12.42% success rate was observed among the patients administered with FSH whereas 9.28% was observed for patients administered with GONAL F. The mean endometrial thickness was observed to be 8.914 mm with a minimum thickness of 4.5 mm and a maximum thickness of 19 mm.Conclusion: The rationale for the use of insemination is to increase gamete density at the site of fertilization. This revealed that intrauterine insemination should be a firstchoice treatment rather than more invasive and expensive techniques of assisted reproduction in cases of cervical, unexplained and moderate male factor subfertility.Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 41-45